2011
DOI: 10.1038/ncomms1320
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Scm3-mediated assembly of budding yeast centromeric nucleosomes

Abstract: Much controversy exists regarding the structural organization of the yeast centromeric nucleosome and the role of the nonhistone protein, Scm3, in its assembly and architecture. Here we show that the substitution of H3 with its centromeric variant Cse4 results in octameric nucleosomes that organize DNA in a left-handed superhelix. We demonstrate by single-molecule approaches, micrococcal nuclease digestion and small-angle X-ray scattering that Cse4-nucleosomes exhibit an open conformation with weakly bound ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
180
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(209 citation statements)
references
References 51 publications
27
180
1
Order By: Relevance
“…It has been previously shown that the Cse4 nucleosome wraps DNA in a right-handed orientation (6,7), consistent with in vivo observations of heterotypic tetrameric nucleosomes in Drosophila (8) and humans (9). However, several studies have shown that CenH3 nucleosomes are left-handed octamers in vitro (10)(11)(12)(13)(14).…”
mentioning
confidence: 71%
“…It has been previously shown that the Cse4 nucleosome wraps DNA in a right-handed orientation (6,7), consistent with in vivo observations of heterotypic tetrameric nucleosomes in Drosophila (8) and humans (9). However, several studies have shown that CenH3 nucleosomes are left-handed octamers in vitro (10)(11)(12)(13)(14).…”
mentioning
confidence: 71%
“…The vast majority of unzipping traces (99%) showed at least one transfer event. For the first such transfer event on each unzipped template (Supplementary Table 2), 67% of traces showed a force signature consistent with that of a nucleosome [10][11][12][13][14][15][16] and 32% were consistent with that of a tetrasome 10,13 , though it is possible that some of these may have been hexasomes 17,18 . These results are in agreement with previous findings that parental H3/H4 tetrasomes generally remain intact after replication fork passage, while H2A/H2B dimers are more labile [19][20][21] .…”
Section: Resultsmentioning
confidence: 99%
“…The resulting unzipping force served as a sensitive detector for the presence of the nucleosome, with a force rise above the naked DNA baseline indicating both nucleosome location and composition (Fig. 1b) [10][11][12][13][14][15][16] . During unzipping, the force first followed that of naked DNA, until the fork reached the positioning sequence, and then a marked force rise characteristic of a canonical nucleosome 11 occurred, followed by a force drop.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations